Effects of microplastics, pesticides and nano-materials on fish health, oxidative stress and antioxidant defense mechanism - Subaramaniyam, Udayadharshini; Allimuthu, Rethi Saliya; Vappu, Shanu; Ramalingam, Divya; Balan, Ranjini; Paital, Biswaranjan; Panda, Niranjan; Rath, Prasana Kumar; Ramalingam, Nirmaladevi; Sahoo, Dipak Kumar (Frontiers in Physiology, 2023)
Microplastics and pesticides are emerging contaminants in the marine biota, which cause many harmful effects on aquatic organisms, especially on fish. Fish is a staple and affordable food source, rich in animal protein, along with various vitamins, essential amino acids, and minerals. Exposure of fish to microplastics, pesticides, and various nanoparticles generates ROS and induces oxidative stress, inflammation, immunotoxicity, genotoxicity, and DNA damage and alters gut microbiota, thus reducing the growth and quality of fish. Changes in fish behavioral patterns, swimming, and feeding habits were also observed under exposures to the above contaminants. These contaminants also affect the Nrf-2, JNK, ERK, NF-κB, and MAPK signaling pathways. And Nrf2-KEAP1 signalling modulates redox status marinating enzymes in fish. Effects of pesticides, microplastics, and nanoparticles found to modulate many antioxidant enzymes, including superoxide dismutase, catalase, and glutathione system. So, to protect fish health from stress, the contribution of nano-technology or nano-formulations was researched. A decrease in fish nutritional quality and population significantly impacts on the human diet, influencing traditions and economics worldwide. On the other hand, traces of microplastics and pesticides in the habitat water can enter humans by consuming contaminated fish which may result in serious health hazards. This review summarizes the oxidative stress caused due to microplastics, pesticides and nano-particle contamination or exposure in fish habitat water and their impact on human health. As a rescue mechanism, the use of nano-technology in the management of fish health and disease was discussed.